SAT0191 Can Spectral Doppler Identify Nail Enthesitis in Psoriatic Arthritis?. (10th June 2014) - Mendonça, J.A.; Nogueira, J.P.; Laurido, I.M.M.; Vierhout, C.; Peron, F.; Lyrio, A.M.; Schincariol, N.B.; Provenza, J.R.; Pedri, L.; Bonfiglioli, R.
Abstract : Background: Inflammatory activity may be quantified using Spectral Doppler (sD), which detects power Doppler (PD) signal through the internal resistance index (RI) in microcirculation 1, 2 . Objectives: Assess the RI in the nail bed in longitudinal (LRI) and transverse (TRI) planes; correlate with the presence of PD in the ungueal bed (NPD), change in standard trilaminar appearance of the nail (NGS), measure of the ungueal bed (mNGS) and clinical measurements. Methods: In this cross-sectional study, 28 patients with psoriatic arthritis (PsA) diagnostic using the CASPAR classification criteria were included, as well as 7 patients control (71.42% healthy and 28.57% with osteoarthritis). They were submitted to an examination through an Esaote Ultrasound machine (Brazil, São Paulo), with 6–18 MHz broadband multifrequency linear transducer and Doppler frequency ranging from 7.1 to 14.3 MHz. The RI was considered changed when measuring ≤0.85 1 . In the statistical study, the program SPSS Statistics 17.0. Spearman's correlation was used to analyze the non-parametric variables and the Pearson's correlation for the analysis of parametric variables. T-test was used for the comparison analysis between the PsA groups and the control. Results: A total of 133 ungueal beds were assessed in patients and control individuals with the following variables: PsA (45.5% men and 54.5% women), race (96.42% Caucasian and 3.57% Asiatic) while controls variables were: 42.9% men, 57.1% women, race (85.71% Caucasians and 14.28% African); the procedure took place in the Instituto de Pesquisa Clínica of Campinas – IPECC and Pontifícia Universidade Catόlica of Campinas. The following average outcomes were observed in the controls: age 37.14±21.59 years; the general visual analog scale for pain (GVASp) 0.00±0.00 cm; LRI 0.86±0.41; TRI 0.70±0.16; NPD 1.0±0.00; mNGS 1.75±0.35 mm; NGS 0.00±0.00. Patients with PsA: 53.57% with no use of medication; 25% using methotrexate (15.71mg ±1.74), 14.28% using anti-TNF and 7.14% acitretin; average outcomes were: disease time 10.05±10.49 years; age 45.3±14.61 years; Psoriasis Area Severity Index (PASI) 6.03±12.27; medication time of use: 11.46±22.00 months; GVASp 1.78±3.42 cm; LRI 0.50±0.13; TRI 0.48±0.09, NPD 0.88±0.31; mNGS 1.73±0.68 mm; NGS 0.48±0.50. Significant correlations: LRI with TRI r=0.333 (p=0.013); mNGS with NGS r=0.472 (p=0.023); LRI with drug time of use r=0.578 (p=0.002) and NGS with disease time r=0.551 (p=0.002). The LRI with NPD showed negative and very low correlation: -0.213 (p=0.038). The TRI with NPD, did not show any correlation (p=0.139). In the comparison between the groups in relation to the RIs: p<0.001 for the PsA group and p=0.002 for the TRI control (Test value = 0.85). Conclusions: The sD may help confirm quantitatively ungueal inflammatory activity in PsA patients in future studies. References: Terslev L, Torp-Pedersen S, Qvistgaard E, von der Recke P, Bliddal H. Doppler ultrasound findings in healthy wrists and finger joints. Ann Rheum Dis 2004; 63:644–648. Gutierrez M, Filippucci E, et al. A sonographic spectrum of psoriatic arthritis: "the five targets". Clin Rheumatol 2009; 29 (2):133-42. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4789